Associations of systemic inflammation and systemic immune inflammation with serum uric acid concentration and hyperuricemia risk: the mediating effect of body mass index - Zhang, Yueyue; Han, Shichao; Duan, Zhizhou; Tian, Xu; Li, Xueyi; Hou, Guangdong; Gao, Xuelin; Tian, Chunjuan; Li, Xiangyu; Yu, Wenyuan; Zhou, Qin; Niu, Zhiping; et al. (Frontiers in Endocrinology, 2024)
Background: With the development of lifestyle, elevated uric acid and hyperuricemia have become important factors affecting human health, but the biological mechanism and risk factors are still unclear. Methods: A multi-stage, cross-sectional study of 41,136 adults from the NHANES 2003-2018 was conducted. Serum uric acid concentrations, platelet, neutrophil, lymphocyte, and monocyte counts were measured. The systemic inflammation response (SIRI) index and systemic immune-inflammatory (SII) index were calculated to reflect systemic inflammation and systemic immune inflammation. The height and weight data were obtained to assess body mass index (BMI). Generalized linear models were used to examine the relationships of SIRI and SII with uric acid and hyperuricemia risk, as well as the associations of SIRI and SII with BMI, and BMI with uric acid and hyperuricemia risk. Causal mediation effect model was used to assess the mediating effect of BMI in the relationships of SIRI, and SII with uric acid concentration and hyperuricemia risk.The prevalence of hyperuricemia in US adults is 19.78%. Positive associations were found in the relationships of SIRI and SII with uric acid level, hyperuricemia risk, and BMI, as well as the relationships of BMI with uric acid and hyperuricemia risk.Causal mediation effect model showed that BMI played an important mediating role in the relationships of SIRI, and SII with uric acid concentration and hyperuricemia risk, with the proportion of mediating effect ranging from 23.0% to 35.9%. 4 Conclusion: Exposure to higher SIRI and SII is associated with increased uric acid concentration and hyperuricemia risk in adults, and BMI plays an important mediating effect. Reducing systemic inflammation and systemic immune inflammation and proper weight control could be effective ways to reduce hyperuricemia prevalence and related health problems.